Measurement of stray neutron doses inside the treatment room from a proton pencil beam scanning system. (February 2017) - Mojżeszek, N.; Farah, J.; Kłodowska, M.; Ploc, O.; Stolarczyk, L.; Waligórski, M.P.R.; Olko, P.
Abstract: Purpose: To measure the environmental doses from stray neutrons in the vicinity of a solid slab phantom as a function of beam energy, field size and modulation width, using the proton pencil beam scanning (PBS) technique. Method: Measurements were carried out using two extended range WENDI-II rem-counters and three tissue equivalent proportional counters. Detectors were suitably placed at different distances around the RW3 slab phantom. Beam irradiation parameters were varied to cover the clinical ranges of proton beam energies (100–220 MeV), field sizes ((2 × 2)–(20 × 20) cm 2 ) and modulation widths (0–15 cm). Results: For pristine proton peak irradiations, large variations of neutron H ∗ (10)/ D were observed with changes in beam energy and field size, while these were less dependent on modulation widths. H ∗ (10)/ D for pristine proton pencil beams varied between 0.04 μSv Gy −1 at beam energy 100 MeV and a (2 × 2) cm 2 field at 2.25 m distance and 90° angle with respect to the beam axis, and 72.3 μSv Gy −1 at beam energy 200 MeV and a (20 × 20) cm 2 field at 1 m distance along the beam axis. Conclusions: The obtained results will be useful in benchmarking Monte Carlo calculations of proton radiotherapy in PBS mode and in estimating the exposure to stray radiation of the patient. Such estimates may be facilitated by the obtained best-fitted simple analytical formulae relating the stray neutron doses at points of interest with beam irradiation parameters.